2005
DOI: 10.1194/jlr.m500103-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Domain-specific lipid distribution in macrophage plasma membranes

Abstract: Lipid rafts, defined as cholesterol-and sphingolipid-rich domains, provide specialized lipid environments understood to regulate the organization and function of many plasma membrane proteins. Growing evidence of their existence, protein cargo, and regulation is based largely on the study of isolated lipid rafts; however, the consistency and validity of common isolation methods is controversial. Here, we provide a detailed and direct comparison of the lipid and protein composition of plasma membrane "rafts" pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 64 publications
5
98
3
Order By: Relevance
“…Conversely, the nonraft proteins tubulin and transferrin receptors are present almost exclusively in the heavier fractions of the gradient. Consistent with other reports (43,44), we also observed that the protein-detergent (Triton X-100) ratio was critical for AChR partitioning in DRMs. A minimal protein-detergent ratio of 1:1 (w/w) was required to recover AChRs within light fractions of the gradients as DRMs.…”
Section: Achr Partitions Within Drms In C2c12 Cellssupporting
confidence: 81%
See 1 more Smart Citation
“…Conversely, the nonraft proteins tubulin and transferrin receptors are present almost exclusively in the heavier fractions of the gradient. Consistent with other reports (43,44), we also observed that the protein-detergent (Triton X-100) ratio was critical for AChR partitioning in DRMs. A minimal protein-detergent ratio of 1:1 (w/w) was required to recover AChRs within light fractions of the gradients as DRMs.…”
Section: Achr Partitions Within Drms In C2c12 Cellssupporting
confidence: 81%
“…Although raft biochemical extraction has raised controversies (52,53), the demonstration by Gaus et al (44) that THP-1 macrophages treated with either 0.2% Triton X-100 or sonication yield membranes of similar lipid structure prompted us to biochemically investigate rafts from C2C12 myotubes. We show here that three different biochemical preparations of DRM fractions using either cold Triton X-100 or detergent-free extraction procedures (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 is expressed and associated with lipid rafts in mouse macrophages (31,35). Caveolae demarcate cholesterol and sphingolipid-rich microdomains of the host cell plasma membrane (36).…”
Section: Caveolin Colocalizes With Francisella Entry Sitesmentioning
confidence: 99%
“…It has been shown that when these two proteins interact, P-gp activity is inhibited (6). However the localization of P-gp in caveolae and its interaction with caveolin-1 remains controversial (7) and could depend on the specific cell line and detergent used in caveolae purification methods (8,9). At present, no studies have looked at caveolin-1 expression at the developing blood-brain barrier (BBB) or how its expression may modulate P-gp function at the developing BBB.…”
mentioning
confidence: 99%